Seven patients with cryptogenic organizing pneumonia succesfully treated with clarithromycin - Çiftci, Fatma; Kumbasar, Özlem Özdemi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Cryptogenic organizing pneumonia is a type of idiopathic interstitial pneumonia with a subacute presentation characterized by variable degrees of cough and dyspnea. As a consequence of the upregulation of inflammatory mediators in cryptogenic organizing pneumonia, it typically responds to anti-inflammatory therapy. Although the majority of patients recover completely with long term oral corticosteroids, relapse is common and their long term use is associated with many adverse effects. Macrolides antiinflammatory agents that appear effective and safe for the treatment of cryptogenic organizing pneumonia. Herein, we analyzed the clinical properties of seven cryptogenic organizing pneumonia patients without severe functional loss who were treated with clarithromycin.